The Black Carbon Dispersion in the Southern Hemisphere and Its Transport and Fate to Antarctica, an Anthropocene Evidence for Climate Change Policies - Cubillos-Montecino, F; Diaz-Robles, L; Santander-Meyer, R (Elsevier B.V., 2021)
Black carbon (BC) has been measured in Antarctica s air, and its global warming effect can potentially speed up the ice melting in the most solid water reservoir of the planet. However, the primary responsible sources are not well evidenced in this region. The dispersion of black carbon emissions from the Southern Hemisphere was conducting using atmospheric chemical transport model and we compared the results with satellite registries from March 1st to April 30th in 2014. The emission inventory considered the anthropogenic and biomass burning emissions from global datasets. The largest and most populated cities in Southern Hemisphere showed the higher emission of BC. As a result, the average daily concentrations of atmospheric BC were around 4 ng/m3 in most regions of Antarctica according to its pristine characteristics. We analyzed fifteen relevant sites in coastal zones of Antartica and some peaks registered by the satellite records were not replicated by model outputs and it was mainly associated with the lack of emissions. Finally, we made simulations in the same period without biomass burning emissions and we observed decreased concentrations of BC in the range of 20–50%. As a result, we show that the black carbon transportation from the continental land to the polar region took place in 17–24 days during the Austral summer and the biomass burning emissions were the primary source. Black Carbon deposition in Antarctica is not permanent, but the uncontrolled emissions from Southern Hemisphere can increase its transportation to the white continent and make its accumulation during the period when the weak polar vortex occurs. © 2021 Elsevier B.V.
Keywords: Black carbon; CMAQ; Antarctica; Biomass burning; Anthropogenic sources; Hemispheric simulation